Ritual use of rosa de borracho (Clinopodium macrostemum (Moc. & Sessé ex Benth.) Kuntze, Lamiaceae) in Oaxaca - DALAY YETLANEZI CALVO-DÍAZ; LISBETH AGUILAR-HERNÁNDEZ; MAYTE STEFANY JIMÉNEZ-NORIEGA; ALEJANDRO TORRES-MONTÚFAR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Calvo-Díaz DY, Aguilar-Hernández L, Jiménez-Noriega MS, Torres-Montúfar A. 2023. Ritual use of rosa de borracho (Clinopodium macrostemum (Moc. & Sessé ex Benth.) Kuntze, Lamiaceae) in Oaxaca. Biodiversitas 24: 5105-5112. Plants play a vital role in the rich tapestry of Mexican culture, serving as medicine, food, clothing, rituals, and construction. Oaxaca is known for its abundance of bio- and cultural diversity, and as such, is home to numerous versatile and beneficial plant species alongside many traditional cultural festivals, including the famous Guelaguetza at the end of every July. Many plants have deep cultural and spiritual significance, and their traditional uses in ceremonies, rituals, and medicine have been passed down through generations. Here, we have studied the ceremonial use of rosa de borracho, or poleo (Clinopodium macrostemum (Moc. & Sessé ex Benth.) Kuntze), in two communities of Oaxaca: Ocotlán de Morelos and Villa Sola de Vega. Semi-structured interviews were conducted with 40 community members to acquire valuable and relevant information about this plant and its importance in these communities. In Villa Sola de Vega, where residents are known as soltecos, the rosa de borracho is an essential element of Soltecan wedding ceremonies, which includes dancing Chilenas (traditional folk music) such as the Jarabe de la Rosa (a dance called syrup of the rose). In this particular dance, the Rosa de Borracho is the show's star, and important guests such as the godparents and cooks are gifted handwoven crowns to wear and bundles of the plant to carry. In Ocotlán, the rosa de borracho is used to adorn baskets and other artifacts for a ceremony called La Llevada del Guajolote, and is also gifted to everyone during the festivities. The same plant is also used on a procession before Christmas and New Year's Eve, wherein pilgrims known as roseros journey to the mountain searching for the plant for use in the day’s celebration. In this study, we have documented and described the ritual use of this plant and its cultural significance to these communities. In conclusion, rosa de borracho carries various symbolic meanings and is often included in sacred offerings to deities or spirits or in ceremonies to adorn altars, decorate ritual spaces, and create intricate floral arrangements, all of which lend it cultural significance in Oaxaca stemming from these ritual practices.